Pengaruh Gini Ratio, Pendapatan per Kapita, Pengeluaran per Kapita, dan UMKM Terhadap IPM Wilayah Pembangunan IV - Hidayati, Widya; Marpaung, Grace Natalia (SAFE-Network, 2025)
This study aims to analyze the influence of the gini ratio, expenditure per capita, GDP per capita, and MSMEs on the human development index in Development Region IV. The research employs a descriptive quantitative approach using panel data, consisting of cross-sectional data from the provinces of Lampung, DKI Jakarta, Central Java, the Special Region of Yogyakarta, dan Banten, as well as time-series data from 2013 to 2022. Data were obtained from BPS, previous research journals, books, and other publications, making the data type in this study secondary. The analysis was conducted using panel linear regression with the Random Effect Model, processed using EViews 12 software. The result indicate that the gini ratio has a positive but insignificant effect on HDI, GDP per capita has a significant negative effect on HDI, expenditure per capita has a significant positive effect on HDI, and MSMEs have a positive but insignificant effect on HDI in Development Region IV during the 2013-2022.